Internalization Of Almaun Values In The Development Of Muhammadiyah Institutions To Improve Service Quality (Case Study: Lazismu, Medan City) - Sirait, Frida Yanti; Pohan, Selamat (Al-Muhtarifin: Islamic Banking and Islamic Economic Journal, 2022)
Aims to Know the Concept of Instilling and Implementing the Internalization of Al-Maun's Values at LAZISMU. This research method uses qualitative research methods, namely in the form of written or spoken words from people and actors who can be observed. This data was obtained from literature studies, interviews and observations to determine the concept of planting and the implementation of the Internalization of Al-Maun's Values at LAZISMU. The results obtained are the concept of embedding Al-Maun's Values in Improving the Quality of Service at LAZISMU Medan City, namely 1) the Concept of Internalizing Al-Maun Values at LAZISMU Medan City, namely through the Method of Habituation of Worship with the concept of empowering orphans and poor people, Strive for social services good service to the people of Medan, especially orphans and needy children and 2) Implementation of the Internalization of Al-Maun Values in improving the quality of services, namely Lazismu in the Implementation of Al-Maun values through the Mentari Scholarship program, namely social care compensation to ensure the continuity of education through parenting in a form of scholarship for students who come from underprivileged families who are followed up every month financed by Lazismu, providing regular basic necessities to the poor from people who pay tithe, infaq and alms